2011
DOI: 10.1155/2011/976262
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Optical Characteristics ofγ-In2Se3Nanorods Grown on Si Substrates

Abstract: This study attempted to grow single-phaseγ-In2Se3nanorods on Si (111) substrates by metal-organic chemical vapor deposition (MOCVD). High-resolution transmission electron microscopy (HRTEM) and selected area electron diffraction (SAED) confirmed that the In2Se3nanorods are singularly crystallized in theγphase. The photoluminescence ofγ-In2Se3nanorods at 15 K was referred to as free and bound exciton emissions. The bandgap energy ofγ-In2Se3nanorods at room temperature was determined to be~1.99 eV, obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The hexagonal phase of γ-In 2 Se 3 has been represented by diffraction peaks such as 25.00° (1 1 0), 27.77° (0 0 6), 30.95° (2 0 2), 43.92° (3 0 0), (ICSD card: 00-023-0294) and 45.98° (1 2 5), 32.35° (2 0 3), 50.10° (1 1 9) (ICSD card: 01–071-0250) respectively. The observed diffraction peaks support the result obtained various workers 26 – 30 . The other peaks at 26.06° (1 0 1), 26.65° (0 1 2) corresponds to rhombohedral phase of InSe (ICSD card: 00–029-0676) have been indexed in the figure.…”
Section: Resultssupporting
confidence: 91%
“…The hexagonal phase of γ-In 2 Se 3 has been represented by diffraction peaks such as 25.00° (1 1 0), 27.77° (0 0 6), 30.95° (2 0 2), 43.92° (3 0 0), (ICSD card: 00-023-0294) and 45.98° (1 2 5), 32.35° (2 0 3), 50.10° (1 1 9) (ICSD card: 01–071-0250) respectively. The observed diffraction peaks support the result obtained various workers 26 – 30 . The other peaks at 26.06° (1 0 1), 26.65° (0 1 2) corresponds to rhombohedral phase of InSe (ICSD card: 00–029-0676) have been indexed in the figure.…”
Section: Resultssupporting
confidence: 91%
“…More recently, it is reported that single-phased In 2 Se 3 nanorods have been successfully grown on Si (111) substrates by the metal-organic chemical vapor deposition (MOCVD) technique. The band gap energy of these nanorods was found to be ∼1.99 eV [10].…”
Section: Introductionmentioning
confidence: 98%